The effectiveness of videoconference-based cognitive-behavioural therapy - Stubbings, Daniel R. (Curtin University, 2012)
The purpose of this research was to expand scientific understanding regarding the use of videoconferencing technology to administer psychological services. The primary study in this thesis is a randomised-controlled trial comparing in-person to videoconference-based Cognitive-Behavioural Therapy (CBT). This study is, to the author’s knowledge, the largest clinical trial investigating the effectiveness of CBT via videoconference that has been conducted on an adult population in Australia. Twenty-nine clients were recruited who had a primary DSM-IV diagnosis of anxiety and/or depression. Participants were randomly assigned to receive 12 sessions of either in-person or videoconference-based treatment. Participants in both conditions received treatment at a university clinic in Perth Western Australia.The intervention provided was based on CBT manualised treatments but individualised to suit the unique needs of each client. Primary symptomology and quality of life was measured pre, post and 6-weeks following treatment. Secondary outcome measures included working alliance, credibility of therapy and client satisfaction. Overall, retention in both treatment conditions was similar. Statistical analysis using multi-level linear modelling indicated a significant reduction in client symptoms across time but no significant differences between treatment conditions. There were also no significant differences between conditions on working alliance, credibility of therapy and client satisfaction ratings. The findings of study one suggest that CBT via videoconference can be effectively provided in a real-world clinical practice context.The second study in this thesis is an in-depth case study of a client with severe and complex obsessive-compulsive disorder who received forty sessions of psychotherapy administered through a mix of videoconference and text-chat. Session recordings, transcripts and therapists notes were analysed using thematic analysis to explore how the technology influenced client engagement. The results indicated that the mixture of videoconferencing and text-chat might have facilitated client engagement by helping to reduce interpersonal anxiety, thus allowing the client to continue disclosing and discussing issues that were espoused in shame, guilt and embarrassment. To the author’s knowledge, the methods of engaging the client via combined videoconference and text-chat reported in study two have not been reported in the literature before.